Consciousness displaced: Art and technology education/collaboration for an aesthetic of liberation. Issue 2 (1st December 2014) - Quinteros, Alejandro
Modernity's grand plans were designed far from where we stand today. The prerogative of progress as an ideological imperative that defined colonialism as a natural balance between the 'developed' societies' moral duty to rescue 'underdeveloped' peoples from their fate of myth and superstition created education. Education that functions as an instrument that is used to facilitate the integration of generations into the logic and aesthetics of the status quo and to bring about conformity to the hegemonic cultural form of western technological consumer capitalism. This article explores whose education and for whom was it created by the imperial ideologies, not of nineteenth- or twentieth-century colonialism but for twenty-first-century western technological consumer neo-colonialism. From South Africa's Apartheid era Liberation before education to Paulo Freire's practice of freedom, this article questions the practices of new technologies, art and technology education at the edge of the disenfranchised. The traditional frameworks of education are on an ideological and methodological crisis worldwide. The hegemony of knowledge has ruptured away from academia. The linearity of thought has burst open as an omni-directional array. The hierarchy of authorship is contested and the audiences are becoming users and participants. As the ubiquity of information technologies, the emergence of connectedness, cheap chips and the presage of the Internet of things permeates every aspect of a particular section of people clustered in specific cities and spread out around the globe, a unique consciousness is evolving where a new collaboration paradigm is gaining a place of balance between us, nature and our technologies, our positions on social justice, and is evolving a symbiotic outlook at other cultures and societies.